Aggressive periodontitis associated with Kindler syndrome in a large Kindler syndrome pedigree - Yildirim, Tuba Talo; Kaya, Filiz Acun; Taskesen, Mustafa; Dundar, Serkan; Bozoglan, Alihan; Tekin, Gulucag Giray; Akdeniz, Sedat (Turkish J Pediatrics, 2017)
Kindler syndrome (KS) is a rare genetic disorder. The clinical features include aggressive periodontal disease and severe desquamative gingivitis. Five individuals with KS were assessed by oral examination, radiographic analysis and periodontal measurements. All the patients' indexes were recorded prior to periodontal treatment and at the end of the 1th, 3th, 6th, 9th and 12th month respectively. All the patients had improvement of periodontal status and enhancement in index scores. The affected individuals were previously screened for FERMT1 mutations. KS patients' periodontal disease activity could be taken under control with regular follow-up.
Keywords: FERMT-1; periodontal disease; periodontal treatment; growth retardation